Interprofessionality in academic training: faculty perspectives in Health-related programs (Brazilian Journal of Health Research, 2024)
Introduction: Interprofessionality in health and the practice of Interprofessional Education (IPE) have provided a new perspective for reorienting training and work practices in health. Objective: To understand the knowledge of professors from the undergraduate courses in Biological Sciences, Nursing, and Pharmacy at a Federal University in the state of Espírito Santo regarding interprofessionality in the context of health education. Method: This is an exploratory and descriptive qualitative research. Twenty-nine professors participated in the study: eight from the Biological Sciences course, twelve from the Nursing course, and nine from the Pharmacy course, all members of the Course Collegiate and the Structuring Teaching Nucleus. Data were analyzed through Content Analysis in the Thematic Analysis modality. Results: The findings indicated that professors from all three courses recognize the relevance of interprofessionality for health education but report several challenges for implementing this approach, such as the lack of training on the subject, difficulties in the teaching-service bond, extensive workload, and the absence of opportunities for interaction between students from different courses. Conclusion: From the professors’ perspectives, the main challenges for interprofessional practice in the context of health education stem from the lack of knowledge on the subject during their educational and professional training, which is mostly explored empirically. However, they acknowledge that interprofessionality is a key factor in the professional development of students.